PEMODELAN SISTEM UNTUK MEREDUKSI WASTE INVENTORI STOK FINISH GOOD AREA PC DENGAN PENDEKATAN LEAN MANUFACTURING DAN SIMULASI PADA PT X - Putu Amelia Pratiwi, (2021)
PT X is a company engaged in manufacture of motorcycle equipment and spare parts. During the pandemic period, PT. X still carried out the same production process pattern that had been carried out so far. So identification is needed to reduce or remove activities that are considered wasteful. This research purpose to provide recommendation using lean manufacturing methods and production system design with system simulation using ProModel software. Lean manufacturing methods used in this research are Value Stream Mapping (VSM) and Value Stream Analysis Tools (VALSAT), fishbone diagrams, and Simulation Model Design. From the results of data processing with this method, there are recommendations for improvements that can reduce lead time by 12,121.186 seconds or 3.36 hours and increase output by 101 units with a percentage increase of 38.99%.